Saudi Civil War (1865-1876) Its causes, consequences and impact on the general conditions in Najd (Journal of the College of Basic Education, 2022)
The research focus on one of the most important period of history of the second Saudi state which is rising of Saudi Civil War (1865-1876). It explain the reasons of war as a consequences of fierce competition between turki bin Abdullah sons and what it leaded to that negatively affected the political , economic and social situation in najed and also intrusion of external forces such as Othman empire and Britain.